Ventilation-perfusion ratio in perflubron during partial liquid ventilation - Scholz, Alexander-Wigbert; Eberle, Balthasar; Heußel, Claus Peter; David, Matthias; Schmittner, Marc; Quintel, Michael; Schreiber, Laura M.; Weiler, Norbert (Anesthesia & analgesia, 2010)
Functional magnetic resonance imaging (fMRI) of fluorine-19 allows for the mapping of oxygen partial pressure within perfluorocarbons in the alveolar space (PAO2). Theoretically, fMRI-detected PAO2 can be combined with the Fick principle approach, i.e., a mass balance of oxygen uptake by ventilation and delivery by perfusion, to quantify the ventilation-perfusion ratio (VA/Q) of a lung region: The mixed venous blood and the inspiratory oxygen fraction, which are equal for all lung regions, are measured. In addition, the local expiratory oxygen fraction and the end capillary oxygen content, both of which may differ between the lung regions, are calculated using the fMRI-detected PAO2. We investigated this approach by numerical simulations and applied it to quantify local VA/Q in the perfluorocarbons during partial liquid ventilation.